THE ETHICAL RESPONSIBILITY OF THE COMMUNICATOR IN PRESS INSTITUTIONS TO CONSOLIDATE THE VALUES OF TOLERANCE: A Study of the Communicator in the Newspapers (Al-Zaman, Al-Sabah, Al-Mada) For the period: 1/5/2020 to 1/10/2020 - Omran, Nada (ALBAHITH ALALAMI, 2022)
This research deals with the role that the media can play in spreading awareness, culture and sound behavior among members of society, due to its ability to reach the largest number of individuals; its wide spread within society; and the moral responsibility of the media in consolidating the components of civil peace. The media works on forming intellectual convictions and behavioral attitudes by publishing opinions and ideas, introducing them to people's awareness and enhancing them in the practice of their daily lives, he was its media medium. Sociologists and psychologists confirm that the media. The significance of the research comes due to the broadening of violence and sectarian fighting; the absence of a culture of civil social peace; and the inability of state institutions, civil society organizations and the media to establish a culture of tolerance and acceptance of the other. Therefore, the national media had to take the initiative to promote a culture of tolerance to reach a state of stability and civil peace. The researcher followed the descriptive approach to reach accurate and useful analytical results in the field of enriching the presented descriptive research studies that depend on content analysis in revealing the topics in question. The spatial domain of research with regard to the moral responsibility of the media is to consolidate the elements of civil peace for the communicator in the media institutions. Whereas, the temporal domain is determined in the period from May 1st, 2020 to October 1st, 2020. As for the human domain, it is 2 represented by the communicator in the Iraqi newspapers (Azzaman, Al-Sabaah, Al-Mada) combined for research. The research reached a set of conclusions, including that the moral responsibility and the promoting of civil peace is one of the most important moral responsibilities of the media; as well as alerting society to the dangers, and employing the media to contribute to civil peace. The effectiveness of publishing issues of coexistence and civil peace is linked to not publishing what is related to race, religion and sect. Highlighting press issues, political and dialogue issues, as well as social ones, all contribute to establishing professional features and transparency for the press away from dealing with sensitive issues such as violence, extremism and rivalry